Social Change and Threat to Agrarian Rights of the Tau Taa Wana Indigenous People in Central Sulawesi - Nutfa, Moh.; Roslinawati, Roslinawati; Mascunra, Andi; Saleh, Moh.; Suriansah, Suriansah (JSW (Jurnal Sosiologi Walisongo), 2023)
Social Change impacts indigenous people socially, which may result in agrarian conflicts and contested land tenure rights between local communities, private parties, and the state. This paper aims to identify social change and explain the negative consequences on the rights of the Tau Taa Wana indigenous people in Central Sulawesi. The article uses a descriptive qualitative research design to collect data through observations, in-depth interviews, focus group discussions, and a literature study. Eight informants became research subjects selected by purposive sampling. The data were analyzed using an interactive model to find patterns of social change and its impacts through data collection, data reduction, data presentation, and verification. Data validity was tested through triangulation. The results showed that 1) the Tau Taa Wana tribe experienced a gradual social transformation from a primitive, nomadic, agrarian society to a modern one, 2) the expansion of oil palm plantations is a modernization that threatened the tenure rights of the tribe, and 3) the Tau Taa Wana tribe will still struggle with agrarian conflicts that render them minority on their land. This research finding suggests the need to voice for agrarian rights in Indonesia as practiced by the Tau Taa Wana indigenous people in Central Sulawesi.